Citogenética clássica e molecular de três espécies de curimatídeos, com ênfase no cromossomo B de Cyphocharax nagelii (Characiformes, Curimatidae) - Oliveira, Rosângela Martins de (2010)
Cyphocharax nagelii, Cyphocharax modestus, and Steindachnerina insculpta were the curimatid species analyzed in the present work. The objectives for all species were to identify sequences that could be used as chromosomal markers, to infer on the active mechanisms in their chromosomal evolution and of the family Curimatidae, and to determine indirectly the nucleotide composition of chromosomal regions. Additionally, the present work also aimed to analyze the B chromosome of C. nagelii, investigating the mitotic and meiotic behavior of this element and making inferences on its origins and evolution. The encountered diploid number was of 2n=54 with meta- and submetacentric chromosomes, corroborating the karyotypic macrostructure of the family Curimatidae. B chromosomes were detected in C. nagelii and analyses indicated that this element is potentially stable during mitosis. The presence of B chromosomes in other curimatid species suggests that this element represents an additional karyotypic differentiation mechanism. In the analyses of metaphase I cells of C. nagelii, the B chromosome behaved as a univalent, indicating possible segregation instability of this element. The C-banding technique evidenced heterochromatin blocks in the pericentromeric region of all chromosomes of the complement, as well as a few telomeric blocks, in the three studied species (B chromosomes in C. nagelii are heterochromatic). No chromosomal heteromorphisms regarding size, morphology, or C-banding pattern that could be associated with the presence of sex chromosomes were found in any of the three curimatid species. Microdissection of the B chromosome and consequent in situ hybridization with the produced probe showed that these elements share many mutual sequences, but the same does not occur with chromosomes of complement A of C. nagelii, C. modestus, or S. insculpta. The use of the base-specific CMA3/DAPI fluorochromes, silver nitrate staining, and 18S rDNA probes allowed the identification of 45S rDNA sites. These sites are present in an autossome pair in the three studied species, as well as in most curimatids. In C. nagelii and C. modestus, the 5S rDNA region is present in chromosome pairs 3 and 20; in S. insculpta only pair 3 contained the 5S rDNA gene. The presence of 5S rDNA in the third pair of the three described species points to a possible conserved location of this gene. A size difference was seen between the 5S rDNA sites, probably owing to the presence of two quantitavely different clusters of this ribosomal sequence. The B chromosomes of C. nagelii do not support 5S or 18S rDNA sequences and were not differentially marked by DAPI or CMA3. The hypothesis that karyotypic evolution in curimatids involves rearrangements of the centric fission/fusion and pericentric inversion type was suggested. Telomeric DNA sequences (TTAGGG)n were used in C. nagelii. The chromosomes of complement A as well as of complement B showed signs in the telomeric region. Furthermore, at least two autosome pairs exhibited telomeric sequences in an interstitial position, thus corroborating the hypothesis of centric fission/fusion evolution combined with pericentric inversion for the family Curimatidae.